Entrepreneurship culture as a factor of strategic socio-economic changes - Лусте Олена, Грунтковський Володимир (Вчені записки Таврійського національного університету імені В.І. Вернадського. Серія: Економіка і управління, 2022)
The article is devoted to research entrepreneurship culture as an important factor of socio-economic transformations. The authors emphasize that the incoherence of the interaction of formal and historically formed informal institutions actualizes the role of entrepreneurship culture, as it directly affects the general vector of the development of the socio-economic system. The article defines that the culture of entrepreneurship determines the dynamics of the development of the institutional environment, affecting the effectiveness of the interaction of formal and informal institutions, ensuring the performance of complementary functions; mediates the process of institutionalization of historically determined values, stereotypes and models of economic behavior in the system of formal norms and rules; ensures, under the influence of other socio-economic factors, the adaptability and dynamism of the institutional structure, promotes the formation and development of new institutions. Authors analyzed the most common methods of measuring the components of the nation's entrepreneurship culture and the selection of the most important international indicators of the efficiency of national economies is substantiated. A structural-logical model of the analysis of the relationship between the components of entrepreneurship culture and indicators of socio-economic development has been developed.
Keywords: entrepreneurial culture, management psychology, strategic development, competitive potential, organizational culture.